Contribution of information and communication technology in increasing agro-based entrepreneurs productivity in Malaysia - Abu Samah, Bahaman; Mohamed Shaffril, Hayrol Azril; Hassan, Md. Salleh; Abu Hassan, Musa (Friends Science Publishers, 2009)
ICT usage has become more relevant in the modern days and agriculture is one of the sectors that benefited from it. ICT without doubt is one of the main instruments in doubling agriculture productivity and agriculture community must be encouraged to utilize it wisely. This paper tends to know the perception of Malaysia agro-based entreprenuers towards the contribution of ICT to their agro-business productivity. Moreover this paper try to discover the factors that affecting this perception. The respondents perceive moderate to high level of contribution of ICT towards their agro-based productivity. Result of the study also highlighted two variables (age & electronic media usage) that significantly influence perceived ICT contribution towards agro-based productivity.